Mitochondrial Protein Synthesis: RNA with the Properties of Eukaryotic Messenger RNA - Perlman, S. (National Academy of Sciences, 1973)
A heterogeneous RNA fraction with properties resembling those of messenger RNA was identified in mammalian mitochondria. Synthesis of contaminating RNA of nuclear origin was suppressed by treatment with camptothecin. Labeling of the messenger-like RNA is completely inhibited by ethidium bromide, a specific inhibitor of mitochondrial functions. Although mitochondrial protein synthesis resembles that of prokaryotes in several regards, the messenger-like RNA is covalently linked to poly(adenylic acid) [poly(A)]. Poly(A) has thus far been found only in eukaryotic cells. The poly(A) segment has a gel electrophoretic mobility of about 4 S, corresponding to a length of 50-80 nucleotides, and thus resembles in size the poly(A) found in some mammalian viral RNAs. The messenger RNA can be released from the mitochondrial protein-synthesizing structure by treatment with puromycin.